2019
DOI: 10.1152/ajpcell.00141.2019
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress pathways in pancreatic β-cells and insulin-sensitive cells and tissues: importance to cell metabolism, function, and dysfunction

Abstract: It is now accepted that nutrient abundance in the blood, especially glucose, leads to the generation of reactive oxygen species (ROS), ultimately leading to increased oxidative stress in a variety of tissues. In the absence of an appropriate compensatory response from antioxidant mechanisms, the cell, or indeed the tissue, becomes overwhelmed by oxidative stress, leading to the activation of intracellular stress-associated pathways. Activation of the same or similar pathways also appears to play a role in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 181 publications
1
135
0
3
Order By: Relevance
“…Insulin insufficiency due to loss of pancreatic β-cells and impairment of their function leads to hypoinsulinemia and hyperglycaemia or diabetes [ 184 ]. It is well recognised that pancreatic β-cells are weak in their antioxidant capacity and thus known to be highly susceptible to OS damage [ 185 ]. Streptozotocin (STZ) has the ability to induce ROS generation as well as DNA damage and therefore is used clinically as a chemotherapeutic agent in the treatment of pancreatic β-cell carcinoma, and is also used experimentally as a diabetogenic agent to induce diabetes-like pathologies in rodents [ 186 ].…”
Section: Trpm2 In Pancreatic Cell Death Associated With Diabetes and mentioning
confidence: 99%
“…Insulin insufficiency due to loss of pancreatic β-cells and impairment of their function leads to hypoinsulinemia and hyperglycaemia or diabetes [ 184 ]. It is well recognised that pancreatic β-cells are weak in their antioxidant capacity and thus known to be highly susceptible to OS damage [ 185 ]. Streptozotocin (STZ) has the ability to induce ROS generation as well as DNA damage and therefore is used clinically as a chemotherapeutic agent in the treatment of pancreatic β-cell carcinoma, and is also used experimentally as a diabetogenic agent to induce diabetes-like pathologies in rodents [ 186 ].…”
Section: Trpm2 In Pancreatic Cell Death Associated With Diabetes and mentioning
confidence: 99%
“…The increased blood serum glucose level is likely due to the pancreatic beta cell damage, as the beta cells are very prone to get damaged by the DMBA. 47,48 However, in the DMBA + P santalinus group, the blood glucose levels reduced significantly as compared with the DMBA group. The reduced blood glucose levels in the DMBA + P santalinus group denotes the hypoglycaemic effect of the plant extract.…”
Section: Discussionmentioning
confidence: 87%
“…High concentration of FFA stimulation can increase the production of highly reactive molecular oxygen clusters and reactive nitrogen clusters, which triggers oxidative stress, prolonged imbalance between the production of highly reactive molecules and anti-oxidant effects resulting in tissue damage. These active molecules can directly oxidize and damage DNA, proteins and lipids, and can also act as functional molecular signals, activating a variety of stress-sensitive signaling pathways in cells, which are closely related to insulin resistance and impaired β-cell function [25,26]. Studies have shown that high levels of FFA lead to a large amount of ROS production and oxidative stress, which can also activate stress-sensitive signaling pathways.…”
Section: Disscussionmentioning
confidence: 99%